Lockdowns and low- and middle-income countries: building a feasible, effective, and ethical COVID-19 response strategy - Oghenowede Eyawo; A. M. Viens; Uchechukwu Chidiebere Ugoji (BMC, 2021)
Abstract Lockdowns can be an effective pandemic response strategy that can buy much needed time to slow disease transmission and adequately scale up preventative, diagnostic, and treatment capacities. However, the broad restrictive measures typically associated with lockdowns, though effective, also comes at a cost - imposing significant social and economic burdens on individuals and societies, especially for those in low- and middle-income countries (LMICs). Like most high-income countries (HICs), many LMICs initially adopted broad lockdown strategies for COVID-19 in the first wave of the pandemic. While many HICs experiencing subsequent waves have returned to employing lockdown strategies until they can receive the first shipments of COVID-19 vaccine, many LMICs will likely have to wait much longer to get comparable access for their own citizens. In leaving LMICs vulnerable to subsequent waves for a longer period of time without vaccines, there is a risk LMICs will be tempted to re-impose lockdown measures in the meantime. In response to the urgent need for more policy development around the contextual challenges involved in employing such measures, we propose some strategies LMICs could adopt for safe and responsible lockdown entrance/exit or to avoid re-imposing coercive restrictive lockdown measures altogether.